IBCOx-17 Safety of Single Stage Revision Laparoscopic Sleeve Gastrectomy Compared to Laparoscopic Roux-Y Gastric Bypass After Failed Gastric Banding. (30th November 2022) - Janik, M; Ibikunle, C; Khan, A; Aryaie, A
Abstract: Background: Reoperation, after failed gastric banding, is a controversial topic. A common approach is band removal with conversion to gastric bypass or sleeve gastrectomy in a single-step procedure. In 2017 the analysis of MBSQAIP Participant User File (PUF) from 2015 revealed that conversion to sleeve gastrectomy might be a safer approach when compared to gastric bypass surgery. We decided to utilize MBSAQIP data from 2015-2018 and replicate the study, addressing critical methodological flaws. This study aimed to assess the safety of revisional surgery to laparoscopic sleeve gastrectomy (LSG) compared to laparoscopic Roux-Y gastric bypass (LRYGB) after failed laparoscopic adjustable gastric banding (LAGB) based on MBSAQIP Participant User File from 2015 to 2018. Methods: Patients who underwent a one-stage conversion of LAGB to LSG (Conv-LSG) or LRYGB (Conv-LRYGB) were identified in the MBSAQIP PUF from 2015 to 2017. Conv - LRYGB cases were matched (1:1) with Conv-LSG patients using propensity scoring to control for potential confounding. The primary outcome was all-cause mortality. Secondary outcomes were readmission, reoperation, intervention, leak and bleed rates, and morbidity. Results: A total of 9 974 patients (4987 matched pairs) were included in the study. The groups were closely matched as intended. was associated with higher risk for readmission Conv-LRYGB, as compared with conv-SG, was associated with a similar risk of mortality (0.02% vs. 0.02%; relative risk [RR], 0.33; 95% confidence interval [CI], 0.03 to 3.20, p=0.32). Conversion to LRYGB increased the risk for readmission (6.16% vs. 3.77%; RR, 1.63; 95%CI, 1.37 to 1.94, p<0.01); reoperation (2.15% vs. 1.36%; RR, 1.57; 95%CI, 1.17 to 2.12, p=<0.01); intervention (3.19% vs. 1.32%; RR, 2.41; 95%CI, 1.82 to 3.19, p<0.01); leak (1.76% vs. 1.02%; RR, 1.57; 95%CI, 1.72 to 2.42, p<0.01); bleeding (1.66% vs. 1.00%; RR, 1.66; 95%CI, 1.7 to 2.34, p<0.01); and morbidity (4.97% vs. 2.35%; RR, 2.12; 95%CI, 1.70 to 2.63, p<0.01). Conclusions: The study confirms that a single stage conversion of failed gastric banding is associated with greater morbidity and higher complication rates when converted to LRYGB versus LSG in the first 30 days postoperatively. These differences are significant with regards to readmission, reoperation, intervention, leak and bleed rates, and morbidity.